Innovations in Promotion Processes: Optimizing the Filling of the List of Proposed Promotions (DUPAK) for Teachers in BPMP D.I. Yogyakarta - Deviana Khoirotun Nisa (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study aims to optimize the List of Proposed Promotions (DUPAK) filling process for teachers at the Education Quality Assurance Agency (BPMP), D.I. Yogyakarta, Indonesia, to enhance transparency, accountability, and quality in the teacher promotion process. Design/methods/approach – A qualitative research approach was employed for this study. Data was gathered from the agency's information system staff using a combination of interviews, observations, and document reviews to understand the existing processes and potential areas of optimization. Findings – The research findings underscore the importance of digitizing DUPAK submissions through the E-PAK application. It has been identified that this digital transformation could promote greater participation and enhance transparency and accountability in the teacher promotion process. Research implications/limitations – This study provides significant insights into the potential for digital transformation in the DUPAK process, thereby potentially improving education quality. However, its insights are confined to one institution, which raises questions about potential barriers and scalability of the process in other educational institutions. Therefore, further research is recommended to explore these aspects and comprehensively understand digital transformation's impact on teachers' career development. Practical implications – The findings have significant practical implications, suggesting a potential direction for educational institutions in optimizing their promotion processes through digital transformation, hence promoting greater transparency, participation and improving the overall quality of education. Originality/value – This study contributes to the existing body of knowledge by exploring the role of digital transformation in enhancing the teacher promotion process. It provides valuable insights into how technology could be leveraged in educational institutions to improve their administrative processes and promote career development.